Principles of political economy and taxation - Ricardo, David (Bell and Sons, 1929)
His clear and consistent definition of the classical system included the foundation of the tenets of diminishing returns and economic rent, which led to the doctrines known today as distribution theory and international trade theory, or comparative advantage. The Ricardian system continues to influence and inform modern economic thought, and The Principles of Political Economy and Taxation is essential reading for students of the social sciences.